Effects of Patterned Sound Deprivation on Short- and Long-Term Plasticity in the Rat Thalamocortical Auditory System In Vivo. (4th January 2016) - Soutar, Chloe N.; Rosen, Laura G.; Rodier, Simon G.; Dringenberg, Hans C.
Abstract : Postnatal sensory experience plays a significant role in the maturation and synaptic stabilization of sensory cortices, such as the primary auditory cortex (A1). Here, we examined the effects of patterned sound deprivation (by rearing in continuous white noise, WN) during early postnatal life on short- and long-term plasticity of adult male rats using an in vivo preparation (urethane anesthesia). Relative to age-matched control animals reared under unaltered sound conditions, rats raised in WN (from postnatal day 5 to 50–60) showed greater levels of long-term potentiation (LTP) of field potentials in A1 induced by theta-burst stimulation (TBS) of the medial geniculate nucleus (MGN). In contrast, analyses of short-term plasticity using paired-pulse stimulation (interstimulus intervals of 25–1000 ms) did not reveal any significant effects of WN rearing. However, LTP induction resulted in a significant enhancement of paired-pulse depression (PPD) for both rearing conditions . We conclude that patterned sound deprivation during early postnatal life results in the maintenance of heightened, juvenile-like long-term plasticity (LTP) into adulthood. Further, the enhanced PPD following LTP induction provides novel evidence that presynaptic mechanisms contribute to thalamocortical LTP in A1 under in vivo conditions.